Regional monetary integration - Kenen, Peter B. 1932-2012 (Cambridge University Press, 2008)
This book surveys the prospects for regional monetary integration in various parts of the world. Beginning with a brief review of the theory of optimal currency areas, it goes on to examine the structure and functioning of the European Monetary Union, then turns to the prospects for monetary integration elsewhere in the world - North America, South America, and East Asia. Such cooperation may take the form of full-fledged monetary unions or looser forms of monetary cooperation. The book emphasizes the economic and institutional requirements for successful monetary integration, including the need for a single central bank in the case of a full-fledged monetary union, and the corresponding need for multinational institutions to safeguard its independence and assure its accountability. The book concludes with a chapter on the implications of monetary integration for the United States and the US dollar